2012
DOI: 10.1242/jcs.089938
|View full text |Cite
|
Sign up to set email alerts
|

The MCM-associated protein MCM-BP is important for human nuclear morphology

Abstract: SummaryMini-chromosome maintenance complex-binding protein (MCM-BP) was discovered as a protein that is strongly associated with human MCM proteins, known to be crucial for DNA replication in providing DNA helicase activity. The Xenopus MCM-BP homologue appears to play a role in unloading MCM complexes from chromatin after DNA synthesis; however, the importance of MCM-BP and its functional contribution to human cells has been unclear. Here we show that depletion of MCM-BP by sustained expression of short hairp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…In addition, a role for MCM-BP in unloading MCM complexes from chromatin at the end of S phase was identified using the Xenopus egg extract system, where MCM-BP depletion resulted in increased levels of MCM proteins on chromatin in mid-to late S phase and MCM-BP was shown to disrupt MCM complexes (23). Similar observations were subsequently made for MCM-BP in human cells (16,22,23). However, the mechanism by which MCM-BP regulates MCM complex unloading is unclear.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In addition, a role for MCM-BP in unloading MCM complexes from chromatin at the end of S phase was identified using the Xenopus egg extract system, where MCM-BP depletion resulted in increased levels of MCM proteins on chromatin in mid-to late S phase and MCM-BP was shown to disrupt MCM complexes (23). Similar observations were subsequently made for MCM-BP in human cells (16,22,23). However, the mechanism by which MCM-BP regulates MCM complex unloading is unclear.…”
supporting
confidence: 71%
“…In human cells, we have shown that MCM-BP depletion results in altered nuclear morphology and replication stress, resulting in G 2 checkpoint activation (16). Similarly, inactivation or loss of the MCM-BP homologues in Schizosaccharomyces pombe (Mcb1) and Arabidopsis thaliana (ETG1) resulted in defects in DNA replication and G 2 checkpoint activation (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Overexpression of the Mcb1 protein or Mcb1 inactivation in temperaturesensitive mcb1 mutants induces DNA damage and G 2 checkpoint activation (29,30). In human cells, the depletion of MCM-BP also leads to centrosome amplification and abnormal nuclear morphology, which may be due to G 2 DNA damage checkpoint activation (31). The loss of A. thaliana ETG1 leads to reduced DNA replication, activation of the G 2 checkpoint, and reduced sister chromatid cohesion (28,32).…”
mentioning
confidence: 99%
“…The depletion of human MCM-BP also leads to reduced sister chromatid cohesion (32). The Xenopus MCM-BP appears to play a role in unloading MCM complexes from chromatin after DNA synthesis (27); however, the depletion of human MCM-BP not only increases the levels of chromatin-associated MCM proteins at the end of S-phase but also leads to a similar increase in soluble levels of MCM proteins throughout S-phase (31), suggesting multiple functions of MCM-BP in DNA replication. The human MCM-BP and A. thaliana ETG1 are largely nuclear throughout the cell cycle (28,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation